Innovative Sol-gel functionalized polyurethane foam for sustainable water purification and analytical advances - Alwael, H.; Alsulami, A. N.; Abduljabbar, T. N.; Oubaha, M.; El-Shahawi, M. S. (Frontiers in Chemistry, 2024)
Nanomaterial combined polymeric membranes such as polyurethane foams (PUFs) have gathered extra attraction to the adoption of water purification due to their ease of management and surface modification, cost-effective, and mechanical, chemical and thermal properties.Thus, the current study reports the use of novel Sol-gel impregnated polyurethane foams (Solgel/PUFs) as new dispersive solid phase microextractors (d-µ SPME) for efficient separation and subsequent spectrophotometric detection of Eosin Y (EY) textile dye in aqueous solution of pH 3-3.8. The Sol gel, PUFs and Sol gel impregnated PUFs were characterized via scanning electron microscopy (SEM), goniometry measurements, dynamic light scattering (DLS), energy dispersive spectroscopy (EDS), UV-Visible and FTIR spectra. Batch experiments results displayed remarkable removal percentage (96±5.4 %) of the EY from the aqueous solution with total sorption time not exceeding 60 min. These data indicative of the rate-limited sorption via diffusion and/or surface complex ion associate formations after rapid initial sorption steps. A pseudo-second order kinetic model thoroughly explained the sorption kinetics, providing sorption capacity (qe) of 37.64 mg g -1 , half-life time (t1/2) of 0.8 ± 0.01 min and intrinsic penetration controls dye retention. The thermodynamic results revealed negative value for ΔG • (-78.07 kJ mol -1 at 293 K) clearly signifying that, the dye uptake was spontaneous as well as negative value for ΔH ⁰ (-69.58 kJ mol -1 ) and positive value of ΔS ⁰ (147.65 J mol -1 K -1 ) making clear the exothermic nature of EY adsorption onto the sorbent with an growth in randomness at a molecular level, respectively. A ternary retention mechanism involving "weak base anion exchanger" of {(-CH2-OH + -CH2-) (Dye anion) -}Sol-gel/PUF and/or {(-NH2 + -COO-) (Dye anion) -} Sol-gel/PUF via solvent extraction; "surface adsorption" of the dye anion on/in the Sol-gel/PUFs membranes in addition to H-bonding including surface complexation and electrostatic π-π interaction resulted between the dye and the silicon/zirconium oxide (Si-O-Zr) and siloxane (Si-O-Si) groups on the sorbent is proposed.